Anomalous variation of electrical transport property and amorphization in dense Alq3. Issue 52 (10th June 2015) - Ke, Feng; Wang, Qinglin; Zhang, Junkai; Guo, Ying; Tan, Dayong; Li, Yan; Liu, Cailong; Han, Yonghao; Ma, Yanzhang; Chen, Xiao-Jia; Chen, Bin; Gao, Chunxiao
<x xml:space="preserve">Abstract</x> The experimental results indicate that the Al–oxine interaction can also be believed to be significant for the electrical transport properties of dense Alq3.